Modeling and experimental validation of material flow during FSW of polycarbonate. (March 2020) - Derazkola, Hamed Aghajani; Eyvazian, Arameh; Simchi, Abdolreza
Abstract: Friction stir welding (FSW) of thermoplastic materials is an attractive but a challenging process due to inherent chemical and mechanical characteristics of polymeric materials. In the present work, thermo-mechanical models were employed to investigate the effect of processing parameters on of FSW of polycarbonate (PC). The heat flux during the joining process was localized around the PC join line and led to the formation of circular rings on the upper surface. According to the simulation results, increasing the tool rotational velocity reduced the temperature gradient and decfeased the suseptibelity of crack formation around the joint line. Cracks were formed at low frictional heats and high strain rates during material stirring. On the other hand, higher heat inputs increased the volume of the preheated material in front of the FSW tool and extruded the material from the leading edge into leading edge. Consequently, less crackes were formed as the plasticized material filed SZ. The results can be used to establish more robust processing parameters for FSW of polymers.